1998
DOI: 10.1046/j.1365-2613.1998.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative histopathology in mouse typhoid among genetically diverse mice

Abstract: Genetically resistant CBA and A/J mice and susceptible BALB/c and C57BL/6 mice were challenged with either an identical infective dose or a minimal lethal dose of Salmonella typhimurium. The histopathological progression of the disease was examined in tissue sections prepared by the JB-4 Plus resin embedding method and compared between the resistant and susceptible mice. In a fatal disease, the lesions in both animal hosts began with focal abscesses within the first three days post infection. Mononuclear cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The liver lesions observed in S. Typhimurium infection in mice (33)(34)(35)(36)(37) are very similar to those described for human typhoid patients (38)(39)(40). We confirmed that systemic infection of naive mice with live S. Typhimurium strain RC60 resulted in extensive liver damage, as shown by large areas of hepatocyte necrosis and infiltration of mononuclear cells (Fig.…”
Section: Resultssupporting
confidence: 85%
“…The liver lesions observed in S. Typhimurium infection in mice (33)(34)(35)(36)(37) are very similar to those described for human typhoid patients (38)(39)(40). We confirmed that systemic infection of naive mice with live S. Typhimurium strain RC60 resulted in extensive liver damage, as shown by large areas of hepatocyte necrosis and infiltration of mononuclear cells (Fig.…”
Section: Resultssupporting
confidence: 85%